Effects of oral desloratadine citrate disodium combined with physiological seawater nasal irrigation on IgE levels, IL-4, IL-6, IL-13 and IFN-Î³ expression and treatment of intermittent allergic rhinitis - Zhang, Yuanyuan; Li, Wei (Cellular and Molecular Biology, 2020)
This experiment was performed to explore the effect of oral desloratadine citrate disodium combined with physiological seawater nasal irrigation in the treatment of intermittent allergic rhinitis and its effect on serum inflammatory factors and peripheral blood Th1 and Th2. For this purpose, 100 patients of intermittent allergic rhinitis admitted to our hospital from January 2018 to January 2020. Randomly divided into a control group (n=50) and an observation group (n=50). The control group was given oral desloratadine citrate disodium. The observation group was given physiological seawater nasal irrigation based on the control group. Both groups were treated for one month. Compare the effect of treatment, symptom and sign scores pre and posttreatment, serum immunoglobulin E (IgE) levels, serum interleukin 4 (IL-4), IL-6, IL-13 and interferon-gamma (IFN-Î³) levels, peripheral blood helper T cells 1 (Th1) and Th2 and the recurrence rate of patients after 1 year between two groups. Results showed that after one month of continuous treatment, the total effective rate of the observation group was significantly higher than that of the control group (P <0.05). The symptoms and signs scores and serum IgE levels of the two groups pretreatment (before treatment) were not significantly different (P > 0.05). The symptoms and signs scores and serum IgE levels of the two groups decreased significantly posttreatment (after treatment) (P <0.05), and the observation group was significantly lower than the control group (P <0.05). Pretreatment, the levels of serum inflammatory factors (IL-4, IL-6, IL-13, and IFN-Î³) and the ratio of peripheral blood Th1 and Th2 to CD4+T cells were not significantly different (P> 0.05). After one month of continuous treatment, the levels of serum IL-4, IL-6, IL-13, and the ratio of peripheral blood CD4+IL-4+/CD4+ in the observation group and the control group were significantly reduced and the ratio of CD4+IFN-Î³+/CD4+ was significantly increased (P <0.05). Compared with the control group, those changes were more obvious in the observation group (P <0.05). The one-year recurrence rate of the observation group was 4% (2/50), which was significantly lower than that of the control group, which was 20% (10/50). There was a statistical difference between the two groups (P <0.05). It was concluded that oral desloratadine citrate disodium combined with physiological seawater nasal irrigation can effectively improve the symptoms and signs of intermittent allergic rhinitis and reduce the recurrence rate. This may be related to balancing T cell responses, promoting systemic Th1 responses and inhibiting Th2 responses, and down-regulating inflammatory response.